Chronic mucocutaneous candidiasis: a look at genetic understanding - Maya Rico, Ana María; Cardona Castro, Nora (Iatreia, 2018)
Chronic mucocutaneous candidiasis is an infectious phenotype characterized by recurrent or persistent infections in the skin, nails and mucous membranes produced by Candida sp. This is secondary to any alteration in the antifungal immunity, in which not only the production of IL-17, but any defect in the differentiation of the T lymphocytes towards their TH17 profile, play a fundamental role and will unchain a susceptibility to this infection; that depending on the genetic etiology, can be a syndromic manifestation with other associated infectious and endocrinological clinical characteristics. Here, we review in a practical, clear and concise manner, the genetic defects so far found to be involved in the appearance of chronic mucocutaneous candidiasis.